Pravastatin and placental insufficiency associated disorders: A systematic review and meta-analysis - Hirsch, Ayala; Rotem, Reut; Ternovsky, Natali; Hirsh Raccah, Bruria (Frontiers in Pharmacology, 2022)
ABSTRACT Background: Uteroplacental insufficiency-associated disorders, such as preeclampsia, fetal growth restriction, and obstetrical antiphospholipid syndrome, share pathophysiology and risk factors with cardiovascular diseases treated with statins. Objective: To evaluate pregnancy outcomes among women with uteroplacental insufficiency disorders who were treated with statins. Search Strategy: Electronic databases were searched from inception to January 2022. Selection Criteria: Cohort studies and randomized controlled trials. Data collection and analysis: Pooled odds ratios were calculated using a random-effects model; meta-regression was utilized when applicable. Main Results: The analysis included ten studies describing 1391 women with uteroplacental insufficiency disorders: 703 treated with pravastatin and 688 not treated with statins. Women treated with pravastatin demonstrated significant prolongation of pregnancy (mean difference 0.44 weeks, 95%CI:0.01-0.87, p=0.04, I2=96%) and less neonatal intensive care unit admissions (OR=0.42, 95%CI: 0.23-0.75, p=0.004, I2=25%). In subgroup analysis, prolongation of pregnancy from study entry to delivery was statistically significant in cohort studies (mean difference 8.93 weeks, 95%CI:4.22-13.95, p=0.00) but not in randomized control studies. Trends were observed toward a decrease in preeclampsia diagnoses (OR=0.54, 95%CI:0.27–1.09, p=0.09, I=44%), perinatal death (OR=0.32, 95%CI:0.09-1.13, p=0.08, I2=54%) and an increase in birth weight (mean difference=102 grams, 95%CI: -14–212, p=0.08, I2=96%). A meta-regression analysis demonstrated an association between earlier gestational age at initiation of treatment and a lower risk of preeclampsia development (R2=1). Conclusions: Pravastatin treatment prolonged pregnancy duration and improved associated obstetrical outcomes in pregnancies complicated with uteroplacental insufficiency disorders in cohort studies.